Morphometric and thermo-physiological diversity in two chicken genotypes kept by rural farmers under tropical conditions - Faith, Elijah Akumbugu; Ogah, Danlami Moses; Yakubu, Abdulmojeed; Bamidele, Oladeji (Acta Scientiarum. Animal Sciences, 2025)
This study investigated phenotypic diversity in indigenous normal feathered and Noiler chickens kept by rural farmers in Nasarawa State, Nigeria. A total of 180 birds at six weeks of age, comprising equal sexes were randomly sampled. Body weight, six primary biometric traits, four morphological indices and four thermo-physiological traits were measured on each bird for six months. The general linear model was used to test the fixed and interaction effects of genotype, sex and location on these traits. Noiler birds had higher (p < 0.05) morphometric traits and morphological indices than indigenous chickens, except for stockiness. Male birds outperformed their female counterparts in body traits and indices, while location effect was also significant. Heat tolerance traits were similar across genotypes, except for higher pulse rate in Noilers. Female birds appeared more stressed thermally while Nasarawa South birds exhibited higher thermal stress. There were significant (p < 0.05) effects of genotype*sex, genotype*location and sex*location interactions on most body parameters, morphological indices and heat tolerance traits. Optimal body weights for both Noiler male and female chickens were predicted at 25.83 and 27.25 weeks. The present findings would provide a basis for the conservation and genetic improvement of both chicken genotypes in Nigeria.